Retextualização de textos acadêmicos: aspectos cognitivos e culturais - Josiane Andrade Militao (2007)
This work aims to analyze to what extent the form of elaboration of a proposal of written academic texts production based on oral academic texts, such as classes and lectures, and the previous exposition of the goals of the class govern the involved cognitive activities in this process of listening and writing. We understand that this analysis involves a work with cognitive and cultural aspects, once that to take the process of textproduction into account, these aspects are intrinsically linked and it is difficult to approach one disrespecting the other. The notion of representation has been considered an epistemological turn on the theories on cognition, and it is reviewed in this work under Biology of Cognition, Anthropological Linguistics and Cognitive Linguistics theories. We have chosen to analyse the data based on the Theory of the Conceptual Blending because it is the one that has presented the best option of representation of the cognitive mapping carried through by the informants in its task of retextualization of academic texts. We analyze two classes of the Course of Letters of the Pontifícia Universidade Católica of Minas Gerais: one where the goals and the conditions of production of the resulting text were previously clear, and another one where neither the goals nor the conditions had been clearly exposed. We analyze the type of conceptual network, the presuppositions and the vital relations constructed by the two different groups of informers. The hypothesis is of that the previous exposition of the classes goals and the conditions of production of the resulting text helps the process of blending of the,compressing mental spaces in a blend, that it is crucial for the understanding. The informers who knew the conditions and the classes goals had presented, in its majority, in accordance with the statistical tests, the best results. We also analyze the form as the groups of informers had recovered the metaphors constructed by the teacher. Ourhypothesis was of that the pupils who had compression difficulties would have to use more metaphorical resources to construct their texts. And that was verified. We leave suggestions for future research here: Are there any vital relations that we establish easier than the others? Which ones? Why? Is the text gender here defined as a leader to the form and the content of the text of the retextualization task proposal is also a defining criterion for the cognitive movements here?